Job satisfaction among Majlis Bandaraya Melaka Bersejarah (MBMB) staffs / Yazlinda Safihi - Safihi, Yazlinda (Faculty of Business and Management, 2005)
The job satisfaction among Majlis Bandaraya Melaka Bersejarah (MBMB) staffs is the focus of the study. Understanding the staffs satisfaction towards the factors influence the job satisfaction. Many of the company today, believe that the staffs are one of their assets. It means that, it is important to make them happy and satisfy to ensure that employees will be loyal with the company. In this research had been done to study the level of job satisfaction and factors that can influence job satisfaction among MBMB staffs. Hopefully, the findings of this research can give some benefits to the company, and they can make some improvement to increase their staffs satisfaction.